Modeling and design of an energy-efficient dual-motor actuation unit with a planetary differential and holding brakes. (February 2018) - Verstraten, Tom; Furnémont, Raphaël; López-García, Pablo; Rodriguez-Cianca, David; Cao, Hoang-Long; Vanderborght, Bram; Lefeber, Dirk
Highlights: Energy-efficient design of a dual-motor actuator with planetary differential. An experimentally validated model of the actuator, including friction and gearbox losses. Analysis of the energy-optimal distribution of the required power over the input motors. The proposed actuator is more energy-efficient than a DC motor with gear reducer. Abstract: By connecting two drivetrains to a single load, a redundant degree of freedom is created. In this work, we investigate how the redundancy of such a system can be exploited in order to make it more energy efficient. The system under study consists of two drivetrains coupled to a planetary differential. Both drivetrains are composed of a geared DC motor and a holding brake. First, we derive an accurate semi-empirical model of this system and prove its validity on a test setup. Based on this model, which includes nonlinear friction terms, we analyze how the power flows and energy losses depend on the redundant degree of freedom. Furthermore, we discuss how the design of the actuator can be optimized for energy efficiency. This strategy is applied to a case study, where a 250 W geared DC motor is replaced by a more efficient dual-motor actuator. Experiments confirm that a dual-motor actuator succeeds in reducing the energy consumption at various loads and speeds. We also show that the results are very sensitive to friction and other speed- and load-dependent losses.